Relationship of Human Personal Characteristics in the three Independent Stratification Systems - Sampil, Tsendsuren; Damba, Tsend-Ayush; Gunchin, Batbaatar; Namjil, Erdenebayar; Dashtsoodol, Nyambayar; Sandag, Tsogtsaikhan (Central Asian Journal of Medical Sciences, 2021)
Objectives: We aimed to analyze theassociation between the biophysiological characteristics of body constitution and temperament type with Mongolian Traditional Medicine (MTM) constitution type to understand further and integrate the application of these stratification systems in clinical medicine. Methods: Body constitution type was classified using the body-mass index, temperament type was determined using personality test, and dominant MTM constitution type was determined in 287 active blood donors. Age, gender, and ABO blood groups were considered as additional biophysiological characteristics. The correlation between the biophysiological characteristics and the nature of their relationship was investigated using likelihood ratio and receiver operating characteristics analysis. Results: Obesity and body-mass index were related to aging, and donor’s age and Badgan expression rate were shown as a sensitive and specific classifier for obesity state. The relationship between Badgan dominant types of human constitutions practiced in Mongolian Traditional Medicine and melancholic temperament was established. Badgan expression was a sensitive and specific classifier for melancholic and phlegmatic temperament. Conclusions: Stratification of human subjects using the primary types of human constitutions practiced in Mongolian Traditional Medicine may be helpful in clinical research and application.